DESIGNING OF INDIVIDUAL EDUCATIONAL TRAJECTORIES IN THE MASTER DEGREE PROGRAM FOR TEACHERS - Irina Igropulo; Alina Dunaenko (Вестник Северо-Кавказского федерального университета)
The article is devoted to the analysis of individualization as the leading strategy of the organization of training in the master degree program for teachers in modern conditions. The characteristic of the reasons complicating realization of idea of an individualization in high schools is given. Individualization is considered as a subject of interdisciplinary research. A comparative analysis of existing theoretical concepts, modern didactic principles is carried out. The essence and structure of an individual educational trajectory is considered. The characteristic of the algorithm for designing an individual educational trajectory is presented, including the diagnostic, target, content, technological, evaluation components. The importance of scientific and methodological support for the design of individual educational trajectories in the open educational space is proved.